Assédio sexual: uma forma de desengajamento moral no ambiente de trabalho das profissionais do sexo - FERREIRA , Priscila Fernanda Santiago (2019)
For a long time mankind has been living with the sex trade, and it has made the dissatisfaction with the existence of such a person remarkable, striving to banish it or to subject it to control and the exercise of power. Even with such attempts, prostitution had once been so important, to the point of contributing to state demands. During its history many were and are depressions, as well as moments of discharge, but prostitution has always been a phenomenon that accompanied and still accompanies human development. The dilemmas about the profession are many among those who accept it as work and those who do not, among these the practice of moral disengagement prevails, a practice studied by the psychologist Albert Bandura, which shows the capacity of the human being to elaborate explanations to justify antisocial acts, in order to eliminate or minimize the sensation of guilt or censorship. So this dissertation aims to analyze the life history of a non-active prostitute and to identify the mechanisms of moral disengagement present in cases of sexual harassment against these professionals. Being a research based on the method of life history, where the life story of an unprofessional sex professional who is reference for the prostitute movement in the state of Maranhão was reported. This study becomes relevant because it will add important data to the Brazilian Prostitution Network, as well as to the organization of prostitutes in Maranhão (APROSMA) and will benefit the Federal University of Maranhão (UFMA) and the Humanities, especially Psychology, with information that will boost future studies, serving as a research source.